Iconography Related to the Mineral-Medicinal Waters in Hispanic Mosaics in Castilla, Aragón and Navarra - Mercedes DURÁN PENEDO (Journal of Mosaic Research, 2018)
This work is dedicated to the memory of Professor José María Blázquez with whom I had a close friendship and whose wise advice helped me to continue my research into the field of mosaics. I will focus on the Hispanic mosaics of Castilla, Aragón and Navarra. We know that gods invoked in thermal spaces ranged from the nymphs to Apollo, Minerva, Jupiter, Juno, Fortune or, for quite some time, even Bormanicus. The image of Medusa was also regarded as the carrier of healing blood, which was kept in the veins of her right arm, and that would be used by Asclepius in his resurrections. On the other hand, it is not unusual to find mosaics with the image of Medusa associated with the gods of hot springs. Objects such as shells, craterae, jars and jugswere part of its symbolic repertoire,which is, in turn, an inexpensive way to represent otherwise more elaborate motifs. In Hispania the said associations are traces of former pre-Roman cults, which would later syncretise with those beliefs imposed by the Roman civilisation. The fact that the higher concentration of mosaics displaying craterae, shells, etc. are located at specific enclaves where waters can be often found in situor not far from the location led us also to believe that there is a connection between the ornamental motifs of mosaics and the curative waters. It will be through this analysis that we will clarify this approach.